Multicenter reproducibility of quantitative susceptibility mapping in a gadolinium phantom using MEDI+0 automatic zero referencing - Deh, Kofi; Kawaji, Keigo; Bulk, Marjolein; Van Der Weerd, Louise; Lind, Emelie; Spincemaille, Pascal; McCabe Gillen, Kelly; Van Auderkerke, Johan; Wang, Yi; Nguyen, Thanh D. (Magnetic resonance in medicine, 2019)
Purpose To determine the reproducibility of quantitative susceptibility mapping at multiple sites on clinical and preclinical scanners (1.5 T, 3 T, 7 T, and 9.4 T) from different vendors (Siemens, GE, Philips, and Bruker) for standardization of multicenter studies. Methods Seven phantoms distributed from the core site, each containing 5 compartments with gadolinium solutions with fixed concentrations between 0.625 mM and 10 mM. Multi‐echo gradient echo scans were performed at 1.5 T, 3 T, 7 T, and 9.4 T on 12 clinical and 3 preclinical scanners. DICOM images from the scans were processed into quantitative susceptibility maps using the Laplacian boundary value (LBV) and MEDI+0 automatic uniform reference algorithm. Region of interest (ROI) analyses were performed by a physicist to determine agreement between results from all sites. Measurement reproducibility was assessed using regression, Bland‐Altman plots, and the intra‐class correlation coefficient (ICC). Results Quantitative susceptibility mapping (QSM) from all scanners had similar, artifact‐free visual appearance. Regression analysis showed a linear relationship between gadolinium concentrations and average QSM measurements for all phantoms (y = 350x – 0.0346, r2>0.99). The SD of measurements increased almost linearly from 32 ppb to 230 ppb as the measured susceptibility increased from 0.26 ppm to 3.56 ppm. A Bland‐Altman plot showed the bias, upper, and lower limits of agreement for all comparisons were −10, −210, and 200 ppb, respectively. The ICC was 0.991 with a 95% CI (0.973, 0.99). Conclusions QSM shows excellent multicenter reproducibility for a large range of susceptibility values encountered in cranial and extra‐cranial applications on a diverse set of scanner platforms.